Pengembangan Teknologi Game Indonesia 3D RPG “The Adventure of Riwut” dengan Unity Engine Berbasis Mobile - Jepli Anuari; Agung Purwanto; Mustaqiem Mustaqiem (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Games have now become an alternative entertainment for various groups. Role Playing Game (RPG) is a game that has elements of a complex story and acting that makes someone feel like a character in the game. This research aims to create a game software in the form of an RPG game using Unity software. The game that is displayed in this final project is based on the folklore of Central Kalimantan entitled